Características dismórficas e desenvolvimento neurocomportamental de filhos de mães com epilepsia generalizada genética após a exposição intraútero aos fármacos antiepilépticos : um estudo observacional - Zetehaku, Ana Carolina [UNIFESP] (2017)
Objective: To analyze pregnancies of mothers with genetic generalized epilepsy (M-GGE) regarding seizure control, treatment, and outcome; cognitive impairment, dysmorphic features (DF), and major congenital malformations (MCMs) in offspring, concerning prenatal exposure to antiepileptic drugs (AEDs), especially valproate (VPA). Methods. Data of 65 pregnancies of 41 M-GGE from a tertiary Brazilian epilepsy outpatient clinic. Groups: (1) pregnancies under VPA monotherapy; (2) polytherapy including VPA; (3) mono/polytherapy without VPA; and (4) without AED. Fifty-three living births were examined for DF/MCMs. Standard photographs from 49 children were analyzed by geneticists to identify DF according to gestalt, determining the presence of fetal valproate syndrome (FVS).Thirty-four children were evaluated with neurodevelopmental tests, 37 with behavioral tests, and 36 using autistic traits screening (AST) tests; 38 M-GGE were submitted to WAIS-R. Results. Group (1) had 19 pregnancies; (2), 16; (3), 15; and (4), 3. During pregnancy, more M-GGE were free from generalized tonic-clonic seizures than previously, especially in the first trimester (p = 0.023). Eleven (22.4%) children fulfilled the criteria for FVS (9 exposed to VPA). MCMs occurred in 17.1% of fetuses exposed to VPA (at least 6 DFs each, minimum dose of 750 mg/day, 4 in polytherapy). Children with FVS had more MCMs (p=0.019). Vineland score was normal in no-FVS children (p=0.033). Two children (18.2%) with FVS showed AST. Neurodevelopmental and behavior tests were not influenced by folic acid supplementation (IQ/mental maturity: p=1.000; CARS: p=0.293; Vineland: p=0.631). Higher maternal IQ (p<0.001) and PHT dose (p=0.006) were associated with AST. Conclusions: FVS prevalence was 11 times that of DF (2%) in Brazilian general population and MCMs 7 times (2-3%). AST was 30 times more frequent than the rate of WHO (0.6%). FVS, MCMs, and AST may not depend on VPA dose.